Microcontroller Based Smart Energy Meter with Data Logger System - Hassan, Kabiru; K. Agboola, Mutiu; A. Oladiran, Taofeek; I. Olorunmaye, Isaac (Journal of Advanced Industrial Technology and Application, 2023)
Recent advancements in power system ensure that energy being generated is efficiently delivered to meet the growing demand for electricity in many countries. However, determining the proper energy usage by the consumers has become a major challenge to utility companies. Metering is an important aspect of electricity distribution, it helps to accurately measure and bill customers for their electricity consumption. In this project, a prototype for an electricity monitoring system using ATMEGA328P as the microcontroller was proposed and developed. The display parameter values are voltage, current, power factor, active and apparent power. A ZMPT101B voltage sensor is used to measure the AC voltage, while an SCT-013 100A current sensor is used to measure the AC current flowing through meter. In addition, a rotary encoder is used to converts the rotational motion into an electrical signal which is used to measure and control various parameters in a system. Real time clock module is based on an internal clock that generates pulses at a fixed frequency. variety of tests to verify that the system can handle the expected volume of data, can communicate reliably and that can secure data were performed such as logging the energy data to memory card, testing input sensors, The voltage and current errors for the energy meter are ±0.1% and ±0.3%, respectively while the power value error of ±0.04%, which is acceptable for most metering devices, The use of smart metering system lead to a more sustainable and efficient energy system for achieving a more sustainable future.